The Impact of Liquidity and Leverage on Profitability with Inflation as an External Factor: A Case Study of Coal Mining Companies on the Indonesia Stock Exchange - Ludiyono, Sugeng; Ahmad Widyan Albajili; Muhammad Tiar (Journal of Business Transformation and Strategy, 2026)
Abstract: This study aims to analyze the impact of the liquidity ratio, proxied by Current Ratio (CR); leverage, proxied by Debt-to-Equity Ratio (DER); and inflation on profitability, proxied by Return on Assets (ROA) of 10 coal mining companies listed on the Indonesia Stock Exchange from 2022 to 2024. The research employs a quantitative approach with panel data regression analysis processed through EViews software. Simultaneously, the results indicate that all three variables significantly influence ROA. However, partially, only inflation has a significant effect, whereas CR and DER show no significant impact. The Adjusted R-Square value of 0.7968 indicates that CR, DER, and inflation collectively explain 79,68% of the variation in ROA, while the remaining 20,32% is explained by factors outside the model. In conclusion, the profitability of the coal mining sector is more heavily driven by external macroeconomic factors than internal managerial factors